Neurological phenomenology of the IRF2BPL mutation syndrome: Analysis of a new case and systematic review of the literature. (July 2022) - Pisano, S.; Melis, M.; Figorilli, M.; Polizzi, L.; Rocchi, L.; Giglio, S.; Defazio, G.; Muroni, A.
Highligths: Epilepsy in IRF2BPL mutation syndrome is expressed in various clinical manifestations. The phenotype in IRF2BPL mutation syndrome is heterogeneous and often includes multiple neurological domains. Abstract: Background: IRF2BPL is an intronless gene that was mapped to 14q24.3 chromosome in 2000 and codes for the interferon regulatory factor 2 binding like protein. Objective: To analyses the clinical characteristics of the patients reported in the literature and of an additional patient we observed in order to better delineate the phenomenological spectrum of the disease and provide indications to improve clinical recognition and facilitate diagnosis. Methods: We reported on 28 patients carrying the IRF2BPL mutation who were identified in 10 papers (n.27), using PUBMED as the search engine, and in our hospital (n. 1). Results: All patients shared developmental delay/regression. Additional neurological symptoms were present in a large proportion of patients and reflected the involvement of five main neurological domains, i.e. epilepsy, dystonia, ataxia, spasticity, and ocular disturbances. Correlation analysis suggested a significant positive correlation between the number of affected neurological domains and the presence of MRI abnormalities (rho = 0.45, p = 0.02), while no significant correlation emerged between the number of affected clinical domains and age at disease onset (rho = 0.18, p = 0.35) or variant type (rho = 0.30, p = 0.12). Conclusions: Our analysis highlights that the IRF2BPL mutation syndrome is highly specific to the central nervous system. Diagnostic work-up should consider the clinical picture of the IRF2BPL mutation syndrome herein delineated and the existence of conditions that share developmental delay/regression and result from acquired/genetic or unidentifiable underlying etiology.